Pustular dermatosis caused by fire ant (Solenopsis invicta) stings in a dog - Conceicao, Lissandro G.; Haddad, Vidal; Loures, Fabricia Hallack (Blackwell Publishing, 2006)
This paper reports a case of spontaneous fire ant sting dermatitis in canine. The skin lesions consisted of nonfollicular, grouped pustules in the abdominal region. Several fire ants were found attached to the lesional skin. Histopathological findings included an intraepidermal neutrophilic pustule and predominantly neutrophilic interstitial dermatitis. An extensive area of collagen degeneration was also observed below the epidermal pustule. These clinical and histopathological findings are remarkable similar to those observed in fire ant stings in humans.